"We are Forgotten": Forced Migration, Sexual and Gender-Based Violence, and Coronavirus Disease-2019. (July 2022) - Phillimore, Jenny; Pertek, Sandra; Akyuz, Selin; Darkal, Hoayda; Hourani, Jeanine; McKnight, Pip; Ozcurumez, Saime; Taal, Sarah
Adopting a structural violence approach, this article explores, with survivors and practitioners, how early coronavirus disease-2019 pandemic conditions affected forced migrant sexual and gender-based violence survivors' lives. Introducing a new analytical framework combining violent abandonment, slow violence, and violent uncertainty, we show how interacting forms of structural violence exacerbated by pandemic conditions intensified existing inequalities. Abandonment of survivors by the state increased precarity, making everyday survival more difficult, and intensified prepandemic slow violence, while increased uncertainty heightened survivors' psychological distress. Structural violence experienced during the pandemic can be conceptualized as part of the continuum of violence against forced migrants, which generates gendered harm.